2017
DOI: 10.15406/jccr.2017.10.00349
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Mitral Annular Plane Systolic Excursion (MAPSE) and Tissue Doppler peak Systolic Velocity with Left Ventricular Systolic Function

Abstract: Background: Estimation of left ventricular function has major diagnostic and prognostic importance in cardiac patients. The most commonly used measure of the systolic function of the left ventricle is ejection fraction (EF), however, the accuracy is limited especially in patients with poor image quality. Mitral annular plane systolic excursion (MAPSE) and tissue Doppler peak systolic velocity (TD PSV) are measurements of longitudinal function which has been shown to correlate with LV global systolic function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Mitral S’ is routinely performed as a part of systolic assessment of the LV, while MAPSE is still not part of comprehensive TTE. The correlation between mitral S’ and LVEF is good-to-excellent among stable cardiac outpatients [ 6 , 11 13 , 31 ]. However, studies in critically ill patients remains limited in sample size, and evidence so far suggests that mitral S’ values are not associated with prognosis in septic patients [ 14 , 15 ], which was confirmed by a recent meta-analysis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitral S’ is routinely performed as a part of systolic assessment of the LV, while MAPSE is still not part of comprehensive TTE. The correlation between mitral S’ and LVEF is good-to-excellent among stable cardiac outpatients [ 6 , 11 13 , 31 ]. However, studies in critically ill patients remains limited in sample size, and evidence so far suggests that mitral S’ values are not associated with prognosis in septic patients [ 14 , 15 ], which was confirmed by a recent meta-analysis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have explored the association between mitral S’ and LVEF and found a good-to-excellent correlation these two variables in non-critically ill patients [ 6 , 11 13 ]. On the other hand, previous studies in critically ill patients have found varied results between these two echocardiographic variables [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mitral s' is routinely available as a part of diastolic assessment of the LV, while MAPSE is still not part of comprehensive TTE. In non-critically ill patients, the correlation between mitral s' and LVEF is good to excellent among stable cardiac outpatients [6, [11][12][13]31]. However, studies in critically ill patients remains limited in sample size, and mitral s' values are not associated with prognosis in septic patients [14,15,32].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have explored the association between mitral S' and LVEF and found a good to excellent correlation these two variables in non-critically ill patients [6, [11][12][13]. On the other hand, previous studies in critically ill patients have found varied results between these two echocardiographic variables [14,15].…”
Section: Introductionmentioning
confidence: 99%